HUBUNGAN LINGKUNGAN KELUARGA DAN PERSEPSI TENTANG PROFESI GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PRODI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS SEBELAS MARET SURAKARTA - Rosmiati, Fajar Dwi; ., Siswandari; ., Sohidin (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe aims of this research are to investigate (1) the correlation between the family environment and the interest in becoming a teacher; (2) the correlation between the perception of teaching as a profession and the interest in becoming a teacher; (3) the correlation of the family environment and the perception of teaching as a profession to the interest in becoming a teacher. This research was conducted at the Accounting Education Department, Teacher Training and Education Faculty, Sebelas Maret University. This research used the descriptive correlational research method. The population consisted of 108 Accounting Education Departmentâs students, years of 2014 and 2015. Simple random sampling method was used to determine the samples. They consisted of 85 students. The data of the research were collected through questionnaire and documentation. The technique of analyzing the data is using correlation and multiple linear regression analysis and being processed through SPSS Windows Version 23. The results of the research are as follows 1) there is positive and significant correlation between family environment and the interest of being a teacher; 2) there is positive and significant correlation between perception of teaching as a profession and the interest in becoming a teacher; 3) there is positive and significant correlation between family environment and the perception of teaching as a profession with the interest in becoming a teacher.Keywords: Family Environment, Perception Of Teaching As A Profession, Interest In Becoming A TeacherABSTRAKPenelitian ini bertujuan untuk menguji 1) hubungan lingkungan keluarga dan minat menjadi guru; 2) hubungan persepsi tentang profesi guru dan minat menjadi guru; 3) hubungan lingkungan keluarga dan persepsi tentang profesi guru terhadap minat menjadi guru. Penelitian ini dilakukan di Prodi Pendidikan Akuntansi FKIP Universitas Sebelas Maret Surakarta menggunakan metode deskriptif korelasional. Populasi adalah mahasiswa pendidikan akuntansi angkatan 2014 dan angkatan 2015 berjumlah 108 mahasiswa. Sampel penelitian diambil dengan teknik simple random sampling sejumlah 85 mahasiswa. Teknik pengumpulan data menggunakan angket dan dokumentasi. Teknik analisis data yang digunakan adalah analisis korelasi dan regresi linear ganda. Analisis data menggunakan SPSS Windows Version 23. Hasil penelitian ini menunjukkan bahwa 1) Ada hubungan positif dan signifikan antara lingkungan keluarga dan minat menjadi guru; 2) Ada hubungan positif dan signifikan antara persepsi tentang profesi guru dan minat menjadi guru; 3) Ada hubungan positif dan signifikan antara lingkungan keluarga dan persepsi tentang profesi guru terhadap minat menjadi guru.Kata Kunci: Lingkungan Keluarga, Persepsi Tentang Profesi Guru, Minat Menjadi Guru